A little Princess - Zamorsky, Tania; Corvino, Lucy; Burnett, Frances Hodgson (New York Sterling Publishing, 2005)
This timeless tale of a poor orphan has won children's hearts for a century--and continues to be a favorite.
Keywords: Tham khảo